Illiberal democratic attitudes and support for the EU. (November 2021) - van der Brug, Wouter; Popa, Sebastian Adrian; Hobolt, Sara B; Schmitt, Hermann
Are those who support the core values of liberal democracy also more likely to support the European Union? In this article, we study the relationship between EU support and support for the principles of liberal democracy among citizens in the 28 EU member states, using data from the European Election Studies 2019. Our findings demonstrate that supporters of liberal principles of democracy tend to be more supportive of the EU, while supporters of more direct forms of citizen influence are more Eurosceptic. We argue that this may be in part due to the design of the EU with strong institutional checks-and-balances, but a weak link to citizens. Attitudes towards liberal democracy are less structured than previous research suggests. Yet, the structuration of attitudes towards liberal democracy and the association between these attitudes and EU support is stronger in contexts where the role of the institutions of liberal democracy is more contested. This reconfirms that elite cues are essential for the formation of structured mass attitudes.